ANALISIS PERMAINAN LABUK JARUM UNTUK PENGEMBANGAN KECERDASAN INTERPERSONAL ANAK USIA 5-6 TAHUN - Vera, Resti; Miranda, Dian; Lukmanulhakim, Lukmanulhakim (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
Interpersonal intelligence is needed by children in the school environment and friendship environment so that children are able to socialize. Efforts that can be made for the development of interpersonal intelligence in early childhood are through playing, one of which is by playing traditional games, namely the Labuk jarum game. This study aims to describe the Labuk jarum Traditional Game for the Development of Interpersonal Intelligence for Children Aged 5-6 Years in Boyan Tanjung Village, Kapuas Hulu District. The method used in this research is descriptive method. The approach used in this research is a qualitative approach. The subjects in this study were early childhood and parents who had played labuk jarum. Data collection techniques used in this study were observation, interviews and documentation. The research results show that: 1. The Labuk jarum game can develop empathic abilities in children aged 5-6 years in Boyan Tanjung Village, Kapuas Hulu District, children show the ability to empathize with their friends which is shown when playing, children want to help their friends, 2. The Labuk jarum game can develop organization abilities in children aged 5-6 years in Boyan Tanjung Village, Kapuas Hulu District, children follow directions or game rules in a structured manner and children can arrange playing rules in a structured manner, 3. The Labuk jarum game can develop the ability to make friends in children aged 5-6 years in the village Boyan Tanjung, Kapuas Hulu District, when children play, they can be seen in relation their peers or other people.